Subassemblage tests and numerical analyses of buckling-restrained braces under pre-compression. (1st May 2017) - Guo, Yan-Lin; Tong, Jing-Zhong; Wang, Xiao-An; Zhang, Bo-Hao
Highlights: Cyclic pure compression and hysteresis tests are conducted. FE results well predict mechanical variables of specimens with a discrepancy less than 3.0%. BRBs with different pre-compression strains are investigated via FE models. Mechanical variables of BRBs obtained from FE analyses provide valuable reference for design. Abstract: Pre-compression loads are conducted in BRBs if the installation of frames and BRBs are performed simultaneously. In this paper, the load-carrying and energy-dissipating behavior of BRBs under pre-compression are investigated by subassemblage tests and additional finite element (FE) analyses. A total of five specimens were tested, in which two specimens were tested by cyclic pure compression loads and three specimens were tested by hysteresis loads; four of them maintained stable load-carrying behavior during loading process. The load-carrying and energy-dissipating behavior of the specimens were satisfactorily simulated using a refined FE model with a combined isotropic and kinematic hardening rule of the core material, and the compression strength adjustment factor and the stress enhancement coefficient were well predicted by the FE analytical results with a relative error less than 3.0%. The FE analytical results of BRBs with different pre-compression strains are presented, indicating that the pre-compression in a BRB would aggravate the stress enhancement of the core material in both tension and compression, yet it would hardly influence the value of the compression strength adjustment factor.